(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2009)
This research aims to Presented model can be applicable – in the frame of current accounting implementations - to measure environmental effects and disclosure then in the financial statements of economic entities after determined the environmental performance scopes of environmental activities that is works by this entities , because of importance of accounting information which presentation by accounting systems which’s effectiveness tool on hand of decision maker about site plans and goals and drawing policies aims protection environment sustainable the represented of naturalism wealth elements . The researcher could be able to application his suggested model which’s proof the ability to environmental accounting measurement and disclosure then.